Preparation method of waterproof and oil-proof ventilation valve for food packaging
By constructing a multi-layered composite structure on the surface of a porous polytetrafluoroethylene film, the problems of rapid attenuation of air permeability and easy liquid leakage in food packaging vent valves in high temperature, high humidity and oily environments are solved, achieving a balance between high air permeability, high barrier properties and long-term durability.
Patent Information
- Application Number
- CN202610021327.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-01-08
- Publication Date
- 2026-02-06
AI Technical Summary
Existing food packaging vent valves suffer from rapid deterioration of permeability and easy liquid leakage in high temperature, high humidity and oily environments due to weak interfacial bonding, poor hydrophilic-hydrophobic balance and contamination accumulation. It is difficult to achieve a balance between high permeability, high barrier properties and long-term durability.
A multi-layered composite structure is constructed on the surface of a porous polytetrafluoroethylene (PTFE) vinyl membrane. Active groups are introduced through plasma activation treatment, which are combined with fluorosilane-modified silica nanoparticles, a fluorinated organosilicon-silica crosslinking layer, and hydrophilic/hydrophobic copolymer chains to form a gradient structure, thereby enhancing the interfacial bonding strength and waterproof and oil-repellent properties.
It achieves a balance between high breathability and excellent waterproof and oil-resistant properties, maintaining high gas and water vapor permeability while significantly improving the breakthrough pressure against water and oily liquids. The breathability and liquid barrier properties remain stable even after multiple high-temperature and high-pressure sterilization processes.
Smart Images

Figure CN121471578A_ABST
Abstract
Description
Technical Field
[0001] This invention relates to the field of membrane technology, and in particular to a method for preparing a waterproof, oil-proof, and breathable valve for food packaging. Background Technology
[0002] During storage, transportation, and sterilization, food packaging containers often experience pressure buildup due to internal temperature changes or gas generation. Vent valves are essential for automatically balancing internal and external pressures to prevent packaging deformation or breakage. Simultaneously, moisture, oils, and other liquids from the external environment can easily penetrate, causing food spoilage. Therefore, vent valves must possess both high air permeability and high liquid barrier properties. However, existing vent valve technology struggles to achieve a stable and sustainable balance between these two aspects, especially under the high-temperature, high-pressure sterilization conditions for oily and water-containing foods.
[0003] Porous polytetrafluoroethylene (PTFE) membranes are widely used as substrates for breathable valves due to their porous structure and chemical inertness, possessing inherent air permeability and hydrophobicity. However, pure PTFE membranes have limited barrier properties against low surface tension liquids (such as edible oils). Oils easily penetrate along the pores, and the membrane surface readily adsorbs contaminants such as proteins and lipids, leading to pore blockage and a gradual decrease in air permeability. This limits their long-term application in oily food packaging.
[0004] To improve water and oil repellency, the industry typically employs surface modification techniques, such as coating PTFE membranes with fluorocarbon resins or silicone compounds. These coatings can temporarily enhance the surface's hydrophobicity and oleophobicity, but the interfacial adhesion between the coating and the PTFE base film is weak, relying mainly on physical adsorption. During mechanical friction, thermal cycling, or autoclaving, the coating is prone to localized peeling or cracking, causing a sharp drop in liquid breakthrough pressure and insufficient durability.
[0005] To address the conflict between breathability and barrier properties, some solutions attempt to introduce hydrophilic components into the coating to maintain moisture permeability, such as adding phosphocholine monomers. However, the introduction of hydrophilic segments often increases surface energy, weakening the barrier against liquid water. Especially in high-temperature and high-humidity environments, the hydrophilic layer is prone to swelling and deformation, which actually accelerates liquid permeation. While a single hydrophobic coating offers better liquid barrier properties, it inhibits the adsorption-diffusion process of water vapor, leading to reduced moisture permeability and failing to meet the breathability requirements of high-humidity food packaging.
[0006] In terms of long-term use, after repeated high-temperature and high-pressure sterilization, the interface fatigue between the coating and the substrate of existing venting valves intensifies, and microcracks easily form at the interface. At the same time, the adsorption and accumulation of oily components on the oleophobic surface gradually clogs the pores, causing a significant decrease in air permeability. These factors make it difficult for existing products to meet the requirements of long-term storage, transportation, and repeated sterilization of foods such as coffee, sauces, and ready-to-eat soups. There is an urgent need for an integrated solution that can synergistically address air permeability, liquid resistance, and durability. Summary of the Invention
[0007] In view of this, the purpose of this invention is to propose a method for preparing and applying a waterproof and oil-proof breathable valve for food packaging, so as to solve the problem that existing food packaging breathable valves, in high temperature, high humidity and oily environments, suffer from weak interfacial bonding, poor hydrophilic-hydrophobic balance and pollution accumulation, resulting in rapid decay of breathability and easy liquid leakage, making it difficult to achieve high breathability, high barrier and long-term durability.
[0008] To achieve the above objectives, the present invention provides a method for preparing a waterproof, oil-proof, and breathable valve for food packaging, comprising the following steps: (1) Plasma activation treatment of porous polytetrafluoroethylene film: radio frequency plasma treatment is performed on both sides of the porous polytetrafluoroethylene film in an oxygen atmosphere to obtain surface activated porous polytetrafluoroethylene film. (2) Preparation of fluorosilane-modified silica nanoparticles: 1H,1H,2H,2H-perfluorodecyltriethoxysilane was hydrolyzed and grafted onto the surface of silica nanoparticles to obtain fluorosilane-modified silica nanoparticles. (3) Preparation of vinyl-containing fluorinated organosilicon-silica sol: Vinyl-containing fluorinated organosilicon-silica sol was prepared by using tetraethoxysilane, vinyltrimethoxysilane, γ-aminopropyltriethoxysilane and fluorosilane modified silica nanoparticles in an acidic anhydrous ethanol / deionized water mixed solution. (4) Construction of fluorinated organosilicon-silica crosslinking layer: The surface-activated porous polytetrafluoroethylene membrane is immersed in fluorinated organosilicon-silica sol containing vinyl groups. Vacuum is drawn under reduced pressure to allow the sol to enter the membrane pores. After the vacuum is released, the immersion is continued. Then, pre-drying and heat curing are carried out in sequence to obtain a composite membrane with fluorinated organosilicon-silica crosslinking layer. (5) Preparation of hydrophilic / hydrophobic comonomer solution: The hydrophilic / hydrophobic comonomer solution was prepared in a methanol / deionized water mixed solvent using a system of 2-methacryloyloxyethyl phosphocholine, 2-(perfluorooctyl)ethyl methacrylate and photoinitiator. (6) Copolymer linking: The composite membrane with the fluorinated organosilicon-silica crosslinking layer is immersed in a hydrophilic / hydrophobic comonomer solution, removed and excess solution is removed from the surface, and free radical polymerization is carried out on both sides of the membrane under ultraviolet light irradiation. Then it is washed and dried to obtain a composite membrane containing copolymer chains and fluorinated organosilicon-silica crosslinking layer. (7) Surface spraying and curing: Deionized water is added to the aqueous two-component fluorocarbon emulsion for dilution, and aqueous blocked aliphatic polyisocyanate crosslinking agent and fluorosilane modified silica nanoparticles are added. The mixture is stirred and ultrasonically dispersed to form a spraying working solution. The working solution is sprayed onto both sides of the composite film containing copolymer chains and fluorinated organosilicon-silica crosslinking layer in sequence. After controlling the wet coating amount, the film is pre-dried and cured under heating conditions to obtain a waterproof, oil-proof and breathable valve for food packaging.
[0009] Preferably, the porous polytetrafluoroethylene vinyl membrane in step (1) has a pore size of 0.2 μm and a thickness of 20 μm.
[0010] Preferably, in the plasma activation treatment in step (1), the radio frequency power is 40-60W, the cavity pressure is 0.1-0.3mbar, and the treatment time is 2-4min per side.
[0011] Preferably, in step (2), the mass ratio of 1H,1H,2H,2H-perfluorodecyltriethoxysilane to silica nanoparticles is 0.8-1.2:8-12.
[0012] Preferably, the average particle size of the silica nanoparticles in step (2) is 20-50 nm.
[0013] Preferably, in step (3), the ratio of tetraethoxysilane, vinyltrimethoxysilane, γ-aminopropyltriethoxysilane, fluorosilane-modified silica nanoparticles and acidic anhydrous ethanol / deionized water mixed solution is 8-12g:3.2-4.8g:1.6-2.4g:4-6g:48.8mL-73.2mL.
[0014] Preferably, in the process of constructing the organosilicon-silica crosslinked layer in step (4), the vacuum pressure is 40-60 kPa and the vacuum time is 3-7 min, the atmospheric pressure impregnation time is 20-40 min, the pre-drying temperature is 80℃ and the time is 8-12 min, and the thermosetting temperature is 110-130℃ and the time is 50-70 min.
[0015] Preferably, in step (5), the ratio of the amount of 2-methacryloyloxyethyl phosphocholine, 2-(perfluorooctyl)ethyl methacrylate and photoinitiator system to methanol / deionized water mixed solvent in the hydrophilic / hydrophobic comonomer solution is 16-24g:16-24g:1.2-2.4g:160-240mL.
[0016] Preferably, the photoinitiator system in step (5) is a mixture of 2-hydroxy-2-methylphenylacetone and benzophenone in a mass ratio of 1:1.
[0017] Preferably, in step (6), the composite membrane with the fluorinated organosilicon-silica crosslinking layer is immersed in the hydrophilic / hydrophobic comonomer solution for 8-12 minutes, the ultraviolet light wavelength is 365 nm, the distance between the membrane and the light source is 10 cm, and the ultraviolet light intensity is 150-250 mW / cm². 2 The irradiation time for each side of the membrane is 8-12 minutes.
[0018] Preferably, in step (7), the mass ratio of the aqueous two-component fluorocarbon emulsion, deionized water, aqueous blocked aliphatic polyisocyanate crosslinking agent and fluorosilane modified silica nanoparticles in the spraying working fluid is 24-36:24-36:1.6-2.4:1.6-2.4.
[0019] Preferably, the wet coating amount during spraying in step (7) is 8-12 g / m². 2 The pre-drying temperature is 80℃ and the time is 8-12 min, and the heat curing temperature is 140-160℃ and the time is 8-12 min.
[0020] Preferably, in step (7), the solid content of the aqueous two-component fluorocarbon emulsion is 40%-50%, and the aqueous blocked aliphatic polyisocyanate crosslinking agent is 55%-65%.
[0021] Furthermore, the present invention also discloses a waterproof and oil-proof breathable valve for food packaging, which is obtained by the preparation method of a waterproof and oil-proof breathable valve for food packaging.
[0022] Furthermore, the present invention also discloses the application of a waterproof and oil-proof breathable valve for food packaging, used to balance the pressure inside and outside the container and prevent water and oil phase liquids from penetrating during high temperature, high pressure and humid heat sterilization.
[0023] The beneficial effects of this invention are: This invention achieves a balance between high air permeability and excellent waterproof and oil-resistant properties by constructing a multi-layered composite structure on the surface of a porous polytetrafluoroethylene membrane. This valve membrane maintains high gas and water vapor permeability while significantly improving the breakthrough pressure for water and oily liquids. Furthermore, its air permeability and liquid barrier properties remain stable even after multiple high-temperature and high-pressure sterilization processes.
[0024] Plasma activation treatment introduces active groups onto the surface of the base film, enhancing the wettability and chemical bonding between the base film and subsequent coatings, thereby improving interfacial bonding strength. This makes the composite layer less prone to peeling under thermal and mechanical stress, improving the structural integrity and durability of the valve diaphragm during cyclic use.
[0025] The fluorinated organosilicon-silica crosslinked layer forms a three-dimensional network framework inside the pores, providing rigid support and multi-point anchoring for the grafted polymer chains. This gradient structure effectively fills pore defects, preventing liquid from penetrating along weak paths, while maintaining coherent gas and water vapor mass transfer channels, ensuring high permeability.
[0026] The synergistic effect of the phosphocholine units and perfluorooctyl segments in the hydrophilic / hydrophobic copolymer chains creates a hydrophilic, antifouling region within the pores, promoting rapid water vapor transport and re-evaporation, while the outer surface maintains its low surface energy superhydrophobic and oleophobic properties. This layered wetting regulation avoids irreversible adsorption of oils and proteins, reduces contaminant accumulation, and ensures long-term stability of breathability.
[0027] Fluorosilane-modified silica nanoparticles introduce micro- and nano-scale rough structures into the cross-linked layer and surface coating, further reducing surface energy and improving the apparent contact angle. Simultaneously, the good compatibility of the modified particles with the organic phase reduces interfacial defects, enhances the overall structural density and mechanical strength, and enables the valve diaphragm to maintain excellent liquid-blocking performance even under harsh environments.
[0028] The surface waterborne fluorocarbon-polyisocyanate crosslinked layer is tightly bonded to the underlying structure through chemical bonding, forming a dense and tough protective layer. This layer not only enhances the initial liquid barrier capability but also maintains its integrity under high temperature and high pressure conditions, effectively delaying aging failure and extending the service life of the valve diaphragm. Attached Figure Description
[0029] To more clearly illustrate the technical solutions in this invention or the prior art, the accompanying drawings used in the description of the embodiments or the prior art will be briefly introduced below.
[0030] Figure 1 The image shows the ATR-FTIR spectrum of the exposed pore section along the thickness direction of the waterproof, oil-proof, and breathable valve for food packaging obtained in Embodiment 2 of the present invention. Detailed Implementation
[0031] To make the objectives, technical solutions, and advantages of this invention clearer, the invention will be further described in detail below with reference to specific embodiments.
[0032] Example 1 Step 1: Plasma activation treatment of porous polytetrafluoroethylene membrane A porous polytetrafluoroethylene (PTFE) film (brand: Sterlitech, catalog number: PTU023001, pore size: 0.2 μm, thickness: 20 μm) was selected as the base film. The film was cut to a size of 100 mm × 100 mm. It was ultrasonically cleaned with anhydrous ethanol for 8 min, rinsed with deionized water for 8 min, and dried in a drying oven at 60 °C for 15 min. The dried porous PTFE film was then placed into the chamber of an experimental radio frequency plasma surface treatment machine. Under an oxygen atmosphere, the radio frequency power was set to 40 W, the chamber pressure to 0.3 mbar, and the treatment time to 2 min per side. One side of the film was treated first, and then the other side was treated. After the treatment, the film was immediately placed in a sealed desiccator to be stored in the dark to obtain a surface-activated porous PTFE film. Step 2: Preparation of fluorosilane-modified silica nanoparticles Weigh 8g of silica nanoparticles (average particle size 30nm) and add them to a pre-prepared mixed solution of 64mL anhydrous ethanol and 16mL deionized water. Disperse the mixture using an ultrasonic disperser for 20min. Then add 1.6mL of 25% ammonia solution to the dispersion, stir magnetically and heat to 65℃. Stir at 65℃ for 45min, then add 0.8g of 1H,1H,2H,2H-perfluorodecyltriethoxysilane. Continue stirring and reacting at 65℃ for 10h. After the reaction is complete, cool the suspension to room temperature and centrifuge at 7000r / min for 8min. Discard the supernatant, resuspend the precipitate in anhydrous ethanol and disperse it ultrasonically for 4min. Wash twice in this manner. Finally, dry the precipitate in a vacuum oven at 55℃ for 10h to obtain fluorosilane-modified silica nanoparticles. Step 3: Preparation of Vinyl-containing Fluorinated Organosilicon-Silica Sol Add 40 mL of anhydrous ethanol and 8 mL of deionized water to a 250 mL beaker, start stirring, and add 8 g of tetraethoxysilane, 3.2 g of vinyltrimethoxysilane and 1.6 g of γ-aminopropyltriethoxysilane in sequence at room temperature. Stir for 15 min, then add 4 g of fluorosilane-modified silica nanoparticles, continue stirring and ultrasonically disperse for 8 min, then add 0.8 mL of 1 mol / L hydrochloric acid aqueous solution, and continue stirring at room temperature for 1.5 h to hydrolyze and polycondense, thus obtaining a vinyl-containing fluorinated organosilicon-silica sol. Step 4: Construction of the fluorinated organosilicon-silica crosslinking layer After fixing the surface-activated porous polytetrafluoroethylene vinyl membrane with a clamp, it was vertically immersed in a vinyl-containing fluorinated organosilicon-silica sol, ensuring that the sol completely submerged the membrane. The membrane was then placed in a vacuum dryer and a vacuum pump was connected to evacuate it to 60 kPa. The vacuum was maintained for 3 minutes. After the vacuum was released, the membrane was immersed for another 20 minutes under normal pressure. The membrane was then slowly removed from the sol, with the removal time controlled at about 45 seconds, allowing excess sol to flow down naturally. The membrane was then hung on a support and left to stand at room temperature for 3 minutes. After that, the membrane was placed in an 80°C oven for pre-drying for 8 minutes, and then transferred to a 110°C oven for heat curing for 50 minutes to obtain a composite membrane with a fluorinated organosilicon-silica crosslinked layer. Step 5: Preparation of hydrophilic / hydrophobic comonomer solution Add 112 mL of methanol and 48 mL of deionized water to a 500 mL beaker. Under stirring at room temperature, add 16 g of 2-methacryloyloxyethyl phosphocholine and 16 g of 2-(perfluorooctyl)ethyl methacrylate in sequence and stir for 20 min. Then add 0.8 g of 2-hydroxy-2-methylphenylacetone and 0.8 g of benzophenone and continue stirring for 20 min to obtain a hydrophilic / hydrophobic comonomer solution. Step 6: Copolymerization of linking branches The composite membrane with a fluorinated organosilicon-silica crosslinking layer was immersed in a hydrophilic / hydrophobic comonomer solution, ensuring complete immersion. It was allowed to stand at room temperature for 8 minutes. After removal, excess solution was gently blotted off with lint-free filter paper. The membrane was then placed horizontally on a quartz plate and placed in a 365nm UV curing chamber, 10cm from the light source, with a UV intensity set to 150mW / cm². 2 After irradiating one side for 8 minutes, the membrane was flipped over and irradiated for another 8 minutes. After the UV irradiation was completed, the membrane was immediately transferred into a stainless steel tank containing 400 mL of methanol / deionized water in a 1:1 volume ratio. The membrane was stirred and washed at room temperature for 20 minutes. The washing solution was discarded, and the same mixture was used to repeat the washing process twice. Finally, the membrane was placed in a 60°C oven and dried for 25 minutes to obtain a composite membrane containing copolymer chains and a fluorinated organosilicon-silica crosslinked layer. Step 7: Surface spraying and curing Add 24g of aqueous two-component fluorocarbon emulsion (45% solids content, model RF-102) to a 250mL beaker, then dilute with 24g of deionized water. Next, add 1.6g of aqueous blocked aliphatic polyisocyanate crosslinking agent (60% solids content, model HD-850), stir for 8 minutes, then add 1.6g of fluorosilane-modified silica nanoparticles and ultrasonically disperse for 8 minutes to obtain the spraying working solution. Fix the composite membrane containing the copolymer chain and the fluoroorganosilicon-silica crosslinking layer horizontally on the spraying stage. Use an air spray gun to evenly spray the above working solution onto one side of the membrane, controlling the wet coating amount to 8g / m². 2After spraying, let it stand at room temperature for 3 minutes, then place the film in an 80℃ oven for 8 minutes to pre-dry, then flip it over and spray the above working solution, controlling the wet coating amount to 8g / m². 2 After spraying, let it stand at room temperature for 3 minutes, then place the film in an 80℃ oven for 8 minutes to pre-dry, and then place it in a 140℃ oven for 8 minutes to heat cure. After cooling to room temperature, a waterproof, oil-proof and breathable valve for food packaging is obtained.
[0033] Example 2: Step 1: Plasma activation treatment of porous polytetrafluoroethylene membrane A porous polytetrafluoroethylene (PTFE) film (brand: Sterlitech, catalog number: PTU023001, pore size: 0.2 μm, thickness: 20 μm) was selected as the base film. The film was cut to a size of 100 mm × 100 mm. It was ultrasonically cleaned with anhydrous ethanol for 10 min, rinsed with deionized water for 10 min, and dried in a drying oven at 60 °C for 20 min. The dried porous PTFE film was then placed into the chamber of an experimental radio frequency plasma surface treatment machine. Under an oxygen atmosphere, the radio frequency power was set to 50 W, the chamber pressure to 0.2 mbar, and the treatment time to 3 min per side. One side of the film was treated first, and then the other side was treated. After the treatment, the film was immediately placed in a sealed desiccator to be stored in the dark to obtain a surface-activated porous PTFE film. Step 2: Preparation of fluorosilane-modified silica nanoparticles Weigh 10g of silica nanoparticles (average particle size 30nm) and add them to a pre-prepared mixed solution of 80mL anhydrous ethanol and 20mL deionized water. Disperse the mixture using an ultrasonic disperser for 30min. Then add 2mL of 25% ammonia water to the dispersion, stir magnetically and heat to 65℃. Stir at 65℃ for 60min, then add 1g of 1H,1H,2H,2H-perfluorodecyltriethoxysilane and continue stirring at 65℃ for 12h. After the reaction is complete, cool the suspension to room temperature and centrifuge at 8000r / min for 10min. Discard the supernatant, resuspend the precipitate in anhydrous ethanol and disperse it ultrasonically for 5min. Wash three times in this way. Finally, dry the precipitate in a vacuum oven at 60℃ for 12h to obtain fluorosilane-modified silica nanoparticles. Step 3: Preparation of Vinyl-containing Fluorinated Organosilicon-Silica Sol Add 50 mL of anhydrous ethanol and 10 mL of deionized water to a 250 mL beaker, start stirring, and add 10 g of tetraethoxysilane, 4 g of vinyltrimethoxysilane and 2 g of γ-aminopropyltriethoxysilane in sequence at room temperature. Stir for 20 min, then add 5 g of fluorosilane-modified silica nanoparticles, continue stirring and ultrasonically disperse for 10 min, then add 1 mL of 1 mol / L hydrochloric acid aqueous solution, and continue stirring at room temperature for 2 h to hydrolyze and polycondense, thus obtaining a vinyl-containing fluorinated organosilicon-silica sol. Step 4: Construction of the fluorinated organosilicon-silica crosslinking layer After fixing the surface-activated porous polytetrafluoroethylene vinyl membrane with a clamp, it was vertically immersed in a vinyl-containing fluorinated organosilicon-silica sol, ensuring that the sol completely submerged the membrane. The membrane was then placed in a vacuum dryer and a vacuum pump was connected to evacuate it to 50 kPa. The vacuum was maintained for 5 minutes. After the vacuum was released, the membrane was immersed for another 30 minutes under normal pressure. The membrane was then slowly removed from the sol, with the removal time controlled at about 60 seconds, allowing excess sol to flow down naturally. The membrane was then hung on a support and left to stand at room temperature for 5 minutes. After that, the membrane was placed in an 80°C oven for pre-drying for 10 minutes, and then transferred to a 120°C oven for heat curing for 60 minutes to obtain a composite membrane with a fluorinated organosilicon-silica crosslinked layer. Step 5: Preparation of hydrophilic / hydrophobic comonomer solution Add 140 mL of methanol and 60 mL of deionized water to a 500 mL beaker. Under stirring at room temperature, add 20 g of 2-methacryloyloxyethyl phosphocholine and 20 g of 2-(perfluorooctyl)ethyl methacrylate in sequence and stir for 30 min. Then add 1 g of 2-hydroxy-2-methylphenylacetone and 1 g of benzophenone and continue stirring for 30 min to obtain a hydrophilic / hydrophobic comonomer solution. Step 6: Copolymerization of linking branches The composite membrane with a fluorinated organosilicon-silica crosslinking layer was immersed in a hydrophilic / hydrophobic comonomer solution, ensuring complete immersion. It was allowed to stand at room temperature for 10 minutes. After removing the membrane, excess solution was gently blotted off with lint-free filter paper. The membrane was then placed horizontally on a quartz plate and placed in a 365nm UV curing chamber, 10cm from the light source, with the UV intensity set to 200mW / cm². 2 After irradiating one side for 10 minutes, the membrane was flipped over and irradiated for another 10 minutes. After the UV irradiation was completed, the membrane was immediately transferred into a stainless steel tank containing 500 mL of methanol / deionized water in a 1:1 volume ratio. The membrane was stirred and washed at room temperature for 30 minutes. The washing solution was discarded, and the same mixture was used to repeat the washing process twice. Finally, the membrane was placed in a 60°C oven and dried for 30 minutes to obtain a composite membrane containing copolymer chains and a fluorinated organosilicon-silica crosslinked layer. Step 7: Surface spraying and curing Add 30g of aqueous two-component fluorocarbon emulsion (45% solids content, model RF-102) to a 250mL beaker, then dilute with 30g of deionized water. Next, add 2g of aqueous blocked aliphatic polyisocyanate crosslinking agent (60% solids content, model HD-850), stir for 10min, then add 2g of fluorosilane-modified silica nanoparticles and ultrasonically disperse for 10min to obtain the spraying working solution. Fix the composite membrane containing the copolymer chain and the fluoroorganosilicon-silica crosslinking layer horizontally on the spraying table, and uniformly spray the above working solution onto one side of the membrane using an air spray gun, controlling the wet coating amount to 10g / m². 2 After spraying, let it stand at room temperature for 5 minutes, then place the film in an 80℃ oven for 10 minutes to pre-dry. Then flip it over and spray the above working solution, controlling the wet coating amount to 10g / m². 2 After spraying, let it stand at room temperature for 5 minutes, then place the film in an 80℃ oven for 10 minutes to pre-dry, and then place it in a 150℃ oven for 10 minutes to heat cure. After cooling to room temperature, a waterproof, oil-proof and breathable valve for food packaging is obtained.
[0034] Example 3: Step 1: Plasma activation treatment of porous polytetrafluoroethylene membrane A porous polytetrafluoroethylene (PTFE) film (brand: Sterlitech, catalog number: PTU023001, pore size: 0.2 μm, thickness: 20 μm) was selected as the base film. The film was cut to a size of 100 mm × 100 mm. It was ultrasonically cleaned with anhydrous ethanol for 12 min, rinsed with deionized water for 12 min, and dried in a drying oven at 60 °C for 25 min. The dried porous PTFE film was then placed into the chamber of an experimental radio frequency plasma surface treatment machine. Under an oxygen atmosphere, the radio frequency power was set to 60 W, the chamber pressure to 0.1 mbar, and the treatment time to 4 min per side. One side of the film was treated first, and then the other side was treated. After the treatment, the film was immediately placed in a sealed desiccator to be stored in the dark to obtain a surface-activated porous PTFE film. Step 2: Preparation of fluorosilane-modified silica nanoparticles Weigh 12g of silica nanoparticles (average particle size 30nm) and add them to a pre-prepared mixed solution of 96mL anhydrous ethanol and 24mL deionized water. Disperse the mixture using an ultrasonic disperser for 40min. Then add 2.4mL of 25% ammonia solution to the dispersion, stir magnetically and heat to 65℃. Stir at 65℃ for 75min, then add 1.2g of 1H,1H,2H,2H-perfluorodecyltriethoxysilane. Continue stirring and reacting at 65℃ for 14h. After the reaction is complete, cool the suspension to room temperature and centrifuge at 9000r / min for 12min. Discard the supernatant, resuspend the precipitate in anhydrous ethanol and disperse it ultrasonically for 6min. Wash four times in this manner. Finally, dry the precipitate in a vacuum oven at 65℃ for 14h to obtain fluorosilane-modified silica nanoparticles. Step 3: Preparation of Vinyl-containing Fluorinated Organosilicon-Silica Sol Add 60 mL of anhydrous ethanol and 12 mL of deionized water to a 250 mL beaker, start stirring, and add 12 g of tetraethoxysilane, 4.8 g of vinyltrimethoxysilane and 2.4 g of γ-aminopropyltriethoxysilane in sequence at room temperature. Stir for 25 min, then add 6 g of fluorosilane-modified silica nanoparticles, continue stirring and ultrasonically disperse for 12 min, then add 1.2 mL of 1 mol / L hydrochloric acid aqueous solution, and continue stirring at room temperature for 2.5 h to hydrolyze and polycondense, thus obtaining a vinyl-containing fluorinated organosilicon-silica sol. Step 4: Construction of the fluorinated organosilicon-silica crosslinking layer After fixing the surface-activated porous polytetrafluoroethylene vinyl membrane with a clamp, it was vertically immersed in a vinyl-containing fluorinated organosilicon-silica sol, ensuring that the sol completely submerged the membrane. The membrane was then placed in a vacuum dryer and a vacuum pump was connected to evacuate it to 40 kPa. The vacuum was maintained for 7 minutes. After the vacuum was released, the membrane was immersed for another 40 minutes under normal pressure. The membrane was then slowly removed from the sol, with the removal time controlled at about 75 seconds, allowing the excess sol to flow down naturally. The membrane was then hung on a support and left to stand at room temperature for 7 minutes. After that, the membrane was placed in an 80°C oven for pre-drying for 12 minutes, and then transferred to a 130°C oven for heat curing for 70 minutes to obtain a composite membrane with a fluorinated organosilicon-silica crosslinked layer. Step 5: Preparation of hydrophilic / hydrophobic comonomer solution Add 168 mL of methanol and 72 mL of deionized water to a 500 mL beaker. Under stirring at room temperature, add 24 g of 2-methacryloyloxyethyl phosphocholine and 24 g of 2-(perfluorooctyl)ethyl methacrylate in sequence and stir for 40 min. Then add 1.2 g of 2-hydroxy-2-methylphenylacetone and 1.2 g of benzophenone and continue stirring for 40 min to obtain a hydrophilic / hydrophobic comonomer solution. Step 6: Copolymerization of linking branches The composite membrane with a fluorinated organosilicon-silica crosslinking layer was immersed in a hydrophilic / hydrophobic comonomer solution, ensuring complete immersion. It was allowed to stand at room temperature for 12 minutes. After removal, excess solution was gently blotted off with lint-free filter paper. The membrane was then placed horizontally on a quartz plate and placed in a 365nm UV curing chamber, 10cm from the light source, with a UV intensity set to 250mW / cm². 2 After irradiating one side for 12 minutes, the membrane was flipped over and irradiated for another 12 minutes. After the UV irradiation was completed, the membrane was immediately transferred into a stainless steel tank containing 600 mL of methanol / deionized water in a 1:1 volume ratio. The membrane was stirred and washed at room temperature for 40 minutes. The washing solution was discarded, and the same mixture was used to repeat the washing process twice. Finally, the membrane was placed in a 60°C oven and dried for 35 minutes to obtain a composite membrane containing copolymer chains and a fluorinated organosilicon-silica crosslinked layer. Step 7: Surface spraying and curing Add 36g of aqueous two-component fluorocarbon emulsion (45% solids content, model RF-102) to a 250mL beaker, then dilute with 36g of deionized water. Next, add 2.4g of aqueous blocked aliphatic polyisocyanate crosslinking agent (60% solids content, model HD-850), stir for 12 minutes, then add 2.4g of fluorosilane-modified silica nanoparticles and ultrasonically disperse for 12 minutes to obtain the spraying working solution. Fix the composite membrane containing the copolymer chain and the fluoroorganosilicon-silica crosslinking layer horizontally on the spraying table, and uniformly spray the above working solution onto one side of the membrane using an air spray gun, controlling the wet coating amount to 12g / m². 2 After spraying, let it stand at room temperature for 7 minutes, then place the film in an 80℃ oven for 12 minutes to pre-dry. Then flip it over and spray the above working solution, controlling the wet coating amount to 12g / m². 2 After spraying, let it stand at room temperature for 7 minutes, then place the film in an 80℃ oven for 12 minutes to pre-dry, and then place it in a 160℃ oven for 12 minutes to heat cure. After cooling to room temperature, a waterproof, oil-proof and breathable valve for food packaging is obtained.
[0035] Comparative Example 1 The difference between Comparative Example 1 and Example 2 is that the porous polytetrafluoroethylene membrane plasma activation treatment step is not performed. Instead, the porous polytetrafluoroethylene membrane without plasma activation treatment is directly cut, cleaned and dried to the same size as in Example 2, and then directly used for the preparation of fluorosilane modified silica nanoparticles. The other conditions are the same as in Example 2.
[0036] Comparative Example 2: The difference between Comparative Example 2 and Example 2 is that the preparation of the vinyl-containing fluorinated organosilicon-silica sol and the construction of the fluorinated organosilicon-silica crosslinking layer are omitted. That is, after the plasma activation treatment of the porous polytetrafluoroethylene membrane is completed, the plasma-activated porous polytetrafluoroethylene membrane is directly immersed in the hydrophilic / hydrophobic comonomer solution used in Example 2 for copolymerization and bonding, and then the surface is sprayed and cured under the same conditions as in Example 2. The remaining conditions are the same as in Example 2.
[0037] Comparative Example 3: The difference between Comparative Example 3 and Example 2 is that 2-methacryloyloxyethyl phosphocholine is not added in the preparation step of the hydrophilic / hydrophobic comonomer solution; instead, it is entirely replaced by 2-(perfluorooctyl)ethyl methacrylate by weight. All other conditions are the same as in Example 2.
[0038] Comparative Example 4: The difference between Comparative Example 4 and Example 2 is that 2-(perfluorooctyl)ethyl methacrylate is not added in the preparation step of the hydrophilic / hydrophobic comonomer solution. Instead, its amount is completely replaced by 2-methacryloyloxyethyl phosphocholine by weight. The other conditions are the same as in Example 2.
[0039] Comparative Example 5: The difference between Comparative Example 5 and Example 2 is that fluorosilane-modified silica nanoparticles are not added in the preparation step of the hydrophilic / hydrophobic comonomer solution; instead, silica nanoparticles are added directly. The other conditions are the same as in Example 2.
[0040] Comparative Example 6: The difference between Comparative Example 6 and Example 2 is that fluorosilane-modified silica nanoparticles are not added when the spraying working fluid is prepared, while the other conditions are the same as in Example 2.
[0041] Performance testing: Fourier transform infrared spectroscopy characterization: The permeable valve prepared in Example 2 was wound along its length onto the outside of a 5mm diameter stainless steel rod. After freezing in liquid nitrogen for 5 minutes, it was rapidly bent to cause brittle fracture of the composite membrane along its thickness, resulting in a cross-section exposing numerous pores. A small cross-section piece of approximately 5mm × 5mm was cut and placed face down on a diamond attenuating total internal reflection crystal. A pressure of 10N was applied using a spring indenter to ensure full and tight contact between the pore wall cross-section and the crystal. Under room temperature conditions, at 4000cm²... -1 -650cm -1 The infrared spectrum of the cross-sectional area is collected to define the scanning range.
[0042] Static water contact angle and soybean oil contact angle: The water contact angle was tested according to GB / T 30693-2014 using an optical contact angle meter. Under the conditions of (23±2)℃ and (50±10)% relative humidity, a 25mm diameter sample was fixed on the sample stage, and a 5.0μL deionized water droplet was dropped onto the surface of each sample using a micro-injection needle. After the water droplet settled, the instrument software automatically fitted the left and right contact angles and took the average value as the result for that point. Five points were tested at different locations for each sample, and the arithmetic mean was taken. The soybean oil contact angle was tested using the same instrument and program, except that the test liquid was changed to food-grade soybean oil. The results are shown in Table 1.
[0043] Air permeability test: The air permeability of the sample was determined according to the method of GB / T 5453-1997 under constant pressure difference mode; during the test, a 25mm diameter diaphragm was fixed on the test head of the air permeability tester, and the effective test area of the sample was 20cm². 2 Adjust the pressure difference between the upper and lower chambers to 200 Pa. Under conditions of (23±2)℃ and (50±10)% relative humidity, record the airflow rate perpendicularly passing through the sample per unit time in a stable state, and calculate the air permeability in L / (m³). 2 Each sample was tested 10 times and the average value was taken. The results are shown in Table 1.
[0044] Water vapor transmission rate test: The test was conducted according to the cup-type weight gain method in GB / T 1037-2021. On the water vapor transmission rate tester, a 40mm × 40mm sample was clamped at the mouth of the permeation cup, exposing the outer side of the membrane to the environment while the inner side contacted the desiccant. The test conditions were: temperature (38±0.5)℃ and relative humidity (90±2)%. The sample was allowed to equilibrate under the test conditions for 2 hours before the test. The mass of the permeation cup was then weighed at 1-hour intervals until the difference in mass gain over three consecutive tests was no greater than 5%. The average weight gain rate was then taken, and the water vapor transmission rate was calculated using the standard formula. The unit is g / (m²). 2 ·d), the results are shown in Table 1.
[0045] Hydrostatic breakthrough pressure of water and soybean oil: Following the principle of GB / T 4744-2013, the water breakthrough pressure of the sample was measured using a hydrostatic tester with a sample area of 100 mm². 2 One side was subjected to a water pressure that increased linearly at 60 cm H2O / min until the third water droplet just formed on the other side, at which point the hydrostatic pressure value was recorded. The soybean oil breakthrough pressure test was conducted with the same equipment and procedures but the test liquid was changed to soybean oil. The results are shown in Table 1.
[0046] Moist heat sterilization durability: Referring to the pressure steam sterilization conditions in the "Disinfection Technical Specifications", samples were assembled on glass bottles containing a standard simulated food system. A 2mm diameter vent hole was pre-drilled in the center of the same specification polypropylene threaded cap, and a 25mm diameter membrane was heat-sealed to the inside of the vent hole. The simulated food system formula was 10% soybean oil, 2% whey protein and 88% deionized water by mass fraction. The sample bottles were placed in a pressure steam sterilizer at 121℃ and 0.12MPa, and each sterilization was maintained for 30 minutes. After sterilization, the bottles were naturally cooled to room temperature. The bottles were then removed and placed in an environment of (23±2)℃ and (50±10)% relative humidity for 24 hours. Ten sterilization cycles were performed continuously. The air permeability of each sample was then measured at a pressure difference of 200Pa. The air permeability retention rate was calculated with the air permeability before sterilization as 100%.
[0047]
[0048] Data Analysis: As can be seen from the data of Examples 1-3 in Table 1, the waterproof and oil-proof breathable valve for food packaging prepared by the present invention is at the level of superhydrophobicity and superoleophobicity in terms of water contact angle and soybean oil contact angle. At the same time, the water breakthrough pressure and soybean oil breakthrough pressure are continuously increased with the reasonable adjustment of the amount of fluorinated organosilicon-silica crosslinking layer and hydrophilic / hydrophobic copolymer chain. The air permeability and water vapor permeability remain in a high and relatively stable range, indicating that the liquid barrier performance is enhanced without significantly sacrificing the air permeability. Based on the retention rate of air permeability after moist heat sterilization, it can be inferred that a synergistic reinforcement structure is formed between the three-dimensional fluorinated organosilicon-silica framework, the grafted phosphocholine / perfluorooctyl copolymer chain, and the surface waterborne fluorocarbon-polyisocyanate crosslinking layer. On the one hand, a continuous mass transfer channel with a certain degree of hydrophilicity is constructed inside the pores, which is conducive to the rapid passage of water vapor and gas. On the other hand, a low surface energy interface with micro-nano dual-scale roughness is formed on the outer surface of the membrane, which significantly improves the breakthrough pressure of water and oil phases. After multiple high temperature and high pressure sterilizations, it can still maintain excellent waterproof, oil-proof and air permeability functions, thus meeting the comprehensive application needs of oily and watery foods such as coffee beans, sauces and ready-to-eat soups in the storage, transportation and sterilization process.
[0049] As can be seen from the data in Table 1 for Example 2 and Comparative Example 1, when the porous polytetrafluoroethylene membrane is not subjected to plasma activation treatment, although the coating system can still form a certain fluorinated organosilicon-silica crosslinked layer and hydrophilic / hydrophobic copolymer chains on the surface of the base membrane, the water contact angle and soybean oil contact angle decrease slightly, the water breakthrough pressure and soybean oil breakthrough pressure decrease significantly, and the air permeability retention rate after moist heat sterilization also decreases significantly. The main reason is that the pore walls of the unactivated porous polytetrafluoroethylene lack polar groups, which restricts the wetting and condensation of the fluorinated organosilicon sol inside the pores. This results in insufficient chemical bonding and mechanical interlocking of the crosslinked skeleton on the pore walls, making it easier for the subsequent grafted segments and aqueous fluorocarbon layer to detach locally or generate microcracks during sterilization and hot-cold cycling. In this case, although the air permeability value is close to that of the embodiment of the present invention, the liquid breakthrough pressure and durability are significantly degraded, indicating that there is an unexpected synergistic effect between plasma activation and the fluorinated organosilicon-silica crosslinking layer. Their combination can significantly improve the interfacial bonding force and long-term liquid resistance without sacrificing air permeability.
[0050] As can be seen from the data in Table 1 for Example 2 and Comparative Example 2, when the steps of preparing the vinyl-containing fluorinated organosilicon-silica sol and constructing the crosslinking layer are omitted, and only the UV copolymerization grafting of hydrophilic / hydrophobic comonomers is performed directly on the plasma-activated porous polytetrafluoroethylene vinyl membrane followed by surface waterborne fluorocarbon spraying, although the water contact angle and soybean oil contact angle of the sample remain at a high level, and the air permeability is even slightly higher than that of Example 2, the water breakthrough pressure and soybean oil breakthrough pressure decrease significantly, and the air permeability retention rate decreases synchronously after moist heat sterilization. The possible reason is that, without the three-dimensional framework of the fluorinated organosilicon-silica that permeates the pores, the copolymer chains are mainly distributed in the thin layer area near the pore opening and the surface. The pore wall lacks rigid support and multi-point covalent anchoring, which makes it easy for local peeling and pore size enlargement to occur under steam sterilization and long-term oil / water immersion conditions. Under the action of pressure difference, the liquid is more likely to penetrate along the defect path. Therefore, it can be seen that constructing a gradient structure in the thickness direction through a fluorinated organosilicon-silica crosslinking layer, so that the grafted chains and water-based fluorocarbon layer are three-dimensionally anchored on the pore skeleton, is the key to achieving both high breakthrough pressure and high air permeability.
[0051] As can be seen from the data in Table 1 for Example 2 and Comparative Example 3, when 2-methacryloyloxyethyl phosphocholine was not added to the hydrophilic / hydrophobic comonomer solution, but instead 2-(perfluorooctyl)ethyl methacrylate was used entirely, the water contact angle and soybean oil contact angle of the sample were further increased, and the surface hydrophobicity and oleophobicity were stronger. However, the air permeability and water vapor permeability were significantly reduced, and the air permeability retention rate after moist heat sterilization was also lower than that in Example 2. The main reason is that the grafted polymer containing only perfluorooctyl segments forms a highly hydrophobic continuous phase in the pores, making it difficult for water vapor to form a uniformly spread film in the pores, thus inhibiting the phase change mass transfer channels. At the same time, the oils and low surface tension components in the food system are prone to strong oleophobic interactions with the perfluorooctyl segments near the pore opening, forming a difficult-to-desorb contaminant layer, which leads to the gradual contraction of the effective gas channels. Conversely, the phosphocholine group introduced in Example 2 constructs a hydrophilic antifouling layer inside the pores, which can promote the rapid spread and re-evaporation of condensate on the pore walls and inhibit the irreversible adsorption of proteins and oils. While maintaining the superhydrophobic outer surface, it increases the gas and water vapor flux and delays the deterioration of contamination, fully demonstrating the synergistic effect of phosphocholine unit and perfluorooctyl segment in interface wetting regulation and antifouling.
[0052] As can be seen from the data in Table 1 for Example 2 and Comparative Example 4, when 2-(perfluorooctyl)ethyl methacrylate was not added to the hydrophilic / hydrophobic comonomer solution, but only 2-methacryloyloxyethyl phosphocholine was used, the air permeability and water vapor transmission rate of the sample were actually higher than those of Example 2 in the dry state. However, the water contact angle and soybean oil contact angle decreased significantly, and the water breakthrough pressure and soybean oil breakthrough pressure decreased significantly. After 10 cycles of moist heat sterilization, the air permeability retention rate was at a low level. The possible reason is that the high enrichment of phosphocholine groups in the pores and near the outer surface makes the interface as a whole strongly hydrophilic. Once the liquid comes into contact with the outer surface, it quickly wets along the pores. Although this is beneficial for water vapor transport, it greatly weakens the barrier ability against water and oil phases. In addition, under repeated high-temperature moist heat sterilization and oil / water alternating immersion conditions, the polymer layer rich in hydrophilic segments undergoes significant swelling and shrinkage. Stress concentration easily induces microcracks and delamination, further reducing the air permeability retention rate. In contrast, Example 2 achieves a layered structure with an inner hydrophilic and an outer superhydrophobic structure by synergistically grafting phosphocholine units and perfluorooctyl segments on the same interface and superimposing an aqueous fluorocarbon-polyisocyanate crosslinking layer. This maintains a high water vapor flux while significantly improving liquid breakthrough pressure and durability.
[0053] As can be seen from the data in Table 1 for Example 2 and Comparative Example 5, when unmodified silica nanoparticles were used to replace fluorosilane-modified silica in the hydrophilic / hydrophobic comonomer solution, the water contact angle and soybean oil contact angle of the sample were significantly lower than those in Example 2. The water breakthrough pressure and soybean oil breakthrough pressure also decreased to some extent, while the changes in air permeability and water vapor transmission rate were relatively small, and the air permeability retention rate after moist heat sterilization was significantly reduced. The main reason for this is that the surface of unmodified silica particles contains a large number of hydroxyl groups, which easily accumulate hydrophilic groups such as phosphocholine during graft polymerization, increasing the local surface energy and weakening the low surface energy interface constructed by the perfluorooctyl segment and the aqueous fluorocarbon layer. At the same time, these highly polar inorganic particles have poor compatibility with fluorine-containing organic phases, and are prone to forming microvoids and interfacial microcracks during thermosetting and sterilization cycles, becoming weak points for liquid penetration and structural fatigue. In contrast, Example 2 pre-modifies silica with fluorosilanes, giving the inorganic particles both low surface energy and good organic phase compatibility. This allows them to play a dual role of roughening and reinforcement in the three-dimensional network, improving both the superhydrophobic and superoleophobic levels and significantly enhancing durability after moist heat sterilization. This demonstrates the synergistic strengthening effect between the modified silica, the fluorinated organosilicon-silica framework, and the waterborne fluorocarbon layer.
[0054] As can be seen from the data in Table 1 for Example 2 and Comparative Example 6, when no fluorosilane-modified silica nanoparticles are added to the spraying working solution, and the surface coating is formed solely by an aqueous two-component fluorocarbon emulsion and an aqueous blocked aliphatic polyisocyanate crosslinking agent, the water contact angle and soybean oil contact angle of the sample are significantly lower than those of Example 2. The water breakthrough pressure and soybean oil breakthrough pressure are also reduced, and the air permeability and water vapor transmission rate are slightly decreased. The air permeability retention rate after moist heat sterilization is lower than that of Example 2, but still better than some other comparative examples. The possible reason is that without fluorosilane-modified silica, the surface of the sprayed coating is only a relatively smooth fluorocarbon polymer crosslinked film, which cannot form a significant micro-nano dual-scale rough structure, resulting in the inability to achieve a higher apparent contact angle and breakthrough pressure under the same low surface energy chemical composition. At the same time, the fluorosilane-modified silica particles in Example 2 not only provide roughness, but also play a bridging role through multi-point crosslinking with the aqueous fluorocarbon resin and the fluorinated organosilicon-silica skeleton, making the surface coating less prone to peeling under moist heat cycling and mechanical stress. Therefore, compared with a single fluorocarbon coating, Comparative Example 6 still does not perform as well as Example 2 in terms of liquid barrier and air permeability stability under long-term sterilization conditions. This further confirms that the ternary synergy between micro-nano particles, fluorocarbon-polyisocyanate crosslinking layer, and underlying organic-inorganic network is the key to achieving a balance of high liquid barrier, high air permeability, and high durability.
[0055] from Figure 1 It can be seen that in the ATR-FTIR spectrum of the exposed pore section along the thickness direction of the waterproof, oil-proof, and breathable valve for food packaging obtained in Example 2, at 1730 cm⁻¹...-1 A distinct strong absorption peak at C=O of the ester / urethane group appears, in the range of 1245-1150 cm⁻¹. -1 and 1205cm -1 A strong absorption band formed by the superposition of P=O, POC, and CF / CF2 stretching vibrations can be observed nearby, at 1100 and 1025 cm⁻¹. -1 The vibrational peaks of the Si-O-Si and Si-OC framework at 3430 cm⁻¹ indicate that the fluorinated organosilicon-silica crosslinking network and the fluorosilane-modified silica nanoparticles have formed a continuous organic-inorganic framework inside the pore walls; simultaneously, the vibrational peaks at 3430 cm⁻¹ indicate that the fluorinated organosilicon-silica crosslinking network and the fluorosilane-modified silica nanoparticles have formed a -1 Broad peak and 2950-2850cm -1 The CH2 / CH3 stretching peak reflects the presence of polar groups introduced by plasma activation and polymethyl methacrylate and fluorocarbon resin segments, 970 cm⁻¹ -1 N at the location + The characteristic peak of (CH3)3 confirms that the phosphocholine group was successfully grafted onto the inner surface of the pore.
[0056] Those skilled in the art should understand that the discussion of any of the above embodiments is merely exemplary and is not intended to imply that the scope of the invention is limited to these examples; within the framework of the invention, the technical features of the above embodiments or different embodiments can also be combined, the steps can be implemented in any order, and there are many other variations of the different aspects of the invention as described above, which are not provided in detail for the sake of brevity.
Claims
1. A method for preparing a waterproof, oil-proof, and breathable valve for food packaging, characterized in that, Includes the following steps: (1) Plasma activation treatment of porous polytetrafluoroethylene film: radio frequency plasma treatment is performed on both sides of the porous polytetrafluoroethylene film in an oxygen atmosphere to obtain surface activated porous polytetrafluoroethylene film. (2) Preparation of fluorosilane-modified silica nanoparticles: 1H,1H,2H,2H-perfluorodecyltriethoxysilane was hydrolyzed and grafted onto the surface of silica nanoparticles to obtain fluorosilane-modified silica nanoparticles. (3) Preparation of vinyl-containing fluorinated organosilicon-silica sol: Vinyl-containing fluorinated organosilicon-silica sol was prepared by using tetraethoxysilane, vinyltrimethoxysilane, γ-aminopropyltriethoxysilane and fluorosilane modified silica nanoparticles in an acidic anhydrous ethanol / deionized water mixed solution. (4) Construction of fluorinated organosilicon-silica crosslinking layer: The surface-activated porous polytetrafluoroethylene membrane is immersed in fluorinated organosilicon-silica sol containing vinyl groups. Vacuum is drawn under reduced pressure to allow the sol to enter the membrane pores. After the vacuum is released, the immersion is continued. Then, pre-drying and heat curing are carried out in sequence to obtain a composite membrane with fluorinated organosilicon-silica crosslinking layer. (5) Preparation of hydrophilic / hydrophobic comonomer solution: The hydrophilic / hydrophobic comonomer solution was prepared in a methanol / deionized water mixed solvent using a system of 2-methacryloyloxyethyl phosphocholine, 2-(perfluorooctyl)ethyl methacrylate and photoinitiator. (6) Copolymer linking: The composite membrane with the fluorinated organosilicon-silica crosslinking layer is immersed in a hydrophilic / hydrophobic comonomer solution, removed and excess solution is removed from the surface, and free radical polymerization is carried out on both sides of the membrane under ultraviolet light irradiation. Then it is washed and dried to obtain a composite membrane containing copolymer chains and fluorinated organosilicon-silica crosslinking layer. (7) Surface spraying and curing: Deionized water is added to the aqueous two-component fluorocarbon emulsion for dilution, and aqueous blocked aliphatic polyisocyanate crosslinking agent and fluorosilane modified silica nanoparticles are added. The mixture is stirred and ultrasonically dispersed to form a spraying working solution. The working solution is sprayed onto both sides of the composite film containing copolymer chains and fluorinated organosilicon-silica crosslinking layer in sequence. After controlling the wet coating amount, the film is pre-dried and cured under heating conditions to obtain a waterproof, oil-proof and breathable valve for food packaging.
2. The method for preparing a waterproof, oil-proof, and breathable valve for food packaging according to claim 1, characterized in that, In step (2), the mass ratio of 1H,1H,2H,2H-perfluorodecyltriethoxysilane to silica nanoparticles is 0.8-1.2:8-12.
3. The method for preparing a waterproof, oil-proof, and breathable valve for food packaging according to claim 1, characterized in that, In step (3), the ratio of tetraethoxysilane, vinyltrimethoxysilane, γ-aminopropyltriethoxysilane, fluorosilane-modified silica nanoparticles, and acidic anhydrous ethanol / deionized water mixed solution is 8-12g:3.2-4.8g:1.6-2.4g:4-6g:48.8-73.2mL.
4. The method for preparing a waterproof, oil-proof, and breathable valve for food packaging according to claim 1, characterized in that, In step (4), during the construction of the organosilicon-silica crosslinking layer, the vacuum pressure is 40-60 kPa and the vacuum time is 3-7 min, the atmospheric pressure impregnation time is 20-40 min, the pre-drying temperature is 80℃ and the time is 8-12 min, and the thermosetting temperature is 110-130℃ and the time is 50-70 min.
5. The method for preparing a waterproof, oil-proof, and breathable valve for food packaging according to claim 1, characterized in that, In step (5), the ratio of the amount of 2-methacryloyloxyethyl phosphocholine, 2-(perfluorooctyl)ethyl methacrylate, and photoinitiator system in the hydrophilic / hydrophobic comonomer solution to the methanol / deionized water mixed solvent is 16-24g:16-24g:1.2-2.4g:160-240mL.
6. The method for preparing a waterproof, oil-proof, and breathable valve for food packaging according to claim 1, characterized in that, In step (6), the composite membrane with the fluorinated organosilicon-silica crosslinking layer is immersed in the hydrophilic / hydrophobic comonomer solution for 8-12 minutes, the ultraviolet wavelength is 365 nm, the distance between the membrane and the light source is 10 cm, and the ultraviolet light intensity is 150-250 mW / cm². 2 The irradiation time for each side of the membrane is 8-12 minutes.
7. The method for preparing a waterproof, oil-proof, and breathable valve for food packaging according to claim 1, characterized in that, In step (7), the mass ratio of the aqueous two-component fluorocarbon emulsion, deionized water, aqueous blocked aliphatic polyisocyanate crosslinking agent, and fluorosilane-modified silica nanoparticles in the spraying working fluid is 24-36:24-36:1.6-2.4:1.6-2.4; the solid content of the aqueous two-component fluorocarbon emulsion is 40%-50%, and the solid content of the aqueous blocked aliphatic polyisocyanate crosslinking agent is 55%-65%.
8. The method for preparing a waterproof, oil-proof, and breathable valve for food packaging according to claim 1, characterized in that, The wet coating amount during spraying in step (7) is 8-12 g / m². 2 The pre-drying temperature is 80℃ and the time is 8-12 min, and the heat curing temperature is 140-160℃ and the time is 8-12 min.
9. A waterproof, oil-proof, and breathable valve for food packaging, characterized in that, It is obtained by the preparation method of the waterproof, oil-proof and breathable valve for food packaging according to any one of claims 1-8.
10. An application of the waterproof, oil-proof, and breathable valve for food packaging according to claim 9, characterized in that, Used to balance the pressure inside and outside the container and prevent the penetration of water and oil phase liquids during high temperature, high pressure and moist heat sterilization.
Citation Information
Patent Citations
Hydrophobic and oleophobic method of porous organic membrane
CN106914150A
Preparation method of polytetrafluoroethylene amphiphobic film
CN109280205A
Package body
CN111319871A
Preparation method of super-amphiphobic waterproof oil-proof breathable film based on synergy of fluorosilane polymer and nanoparticles
CN114805894A
Water-based bionic super-hydrophobic self-cleaning coating as well as preparation method and application thereof
CN120329801A
Cited By
Silicone rubber anti-skid material for food shoes and preparation method of silicone rubber anti-skid material
CN122080646A
